Targeting the tumor microenvironment with protein-small molecule hybrids - Kehoe, Haixing. (2018)
Abstract: In cancer, changes in enzyme expression levels and activity levels lead to a complex, altered microenvironment that promotes unregulated cell growth, angiogenesis, and metastasis. The biology of the tumor microenvironment, including the roles of the proteases and peptidases involved, remains poorly characterized. Evaluating the functions of these enzymes is challenging due to the absence of specific inhibitors. Previous studies have developed protein binders, such as antibodies, which can bind specifically to a unique enzyme, but these binders are rarely able to inhibit enzymatic activity. On the other hand, small molecules can bind to the active site of an enzyme, but these compounds often inhibit a wide range of closely related proteases and peptidases. The objective of this work is to create a new class of specific enzyme inhibitors consisting of a protein binder conjugated to a small molecule. A new synthetic antibody library was developed, characterized, and successfully enriched for binders to various antigens. Additionally, protein-small molecule hybrids were rationally designed and constructed using click chemistry. Protein-small molecule hybrids were tested for their ability to bind to unique enzymes compared to their single chain variable fragment (scFv) counterparts. The methodology proposed in this work will result in novel enzymatic inhibitors to evaluate the complexity of the tumor microenvironment and may also result in the generation of new class of therapeutics.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: James Van Deventer.; Committee: Kyongbum Lee, and Joshua Kritzer.; Keywords: Biomedical engineering, Molecular biology, and Chemical engineering.